2014
DOI: 10.5586/asbp.1998.009
|View full text |Cite
|
Sign up to set email alerts
|

Rhodiola rosea in vitro culture - phytochemical analysis and antioxidant action

Abstract: Various Rhodiola rosea organs and tissues from in vitro culture were studied in two areas: searching for the biological active four phenolic compounds and measurement of antioxidant activity of dry residues of EtOH-extracts soluble in PBS using chemiluminescence method. For phytochemical investigation HPLC method was used. Salidroside was typical for organs of intact plant, rosavin for roots of different origin and shoots of intact plants, triandrin was more typical for tissue cultured in vitro, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Previous studies have investigated the immunotropic activity of alcoholic and aqueous extracts of roots and rhizomes of Rhodiola plants in mice, rats and pigs. During the initial investigation (11), not a large quantity of information was available about the immunotropic activity of Rhodiolas. Further studies showed that the majority of Rhodiola extracts stimulated immunity (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the immunotropic activity of alcoholic and aqueous extracts of roots and rhizomes of Rhodiola plants in mice, rats and pigs. During the initial investigation (11), not a large quantity of information was available about the immunotropic activity of Rhodiolas. Further studies showed that the majority of Rhodiola extracts stimulated immunity (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our studies have shown that extracts from plants belonging to Rhodiola species can enhance various in vitro and in vivo parameters of cellular immunity in mice, rats and pigs, which has become a goal for research (Furmanowa et al 1998, Siwicki et al 2007, Skopińska-Różewska et al 2008d, 2010, 2011, Wójcik et al 2008, 2009a,b,c, Bany et al 2009, Hartwich 2010, Zdanowski et al 2014, Lewicki et al 2015.…”
Section: Discussionmentioning
confidence: 98%
“…It grows mainly in dry sandy ground at high altitudes in the arctic areas of Europe and Asia, Traditional folk medicine used R. rosea to increase physical endurance, work productivity, longevity, resistance to high altitude sickness, and to treat fatigue, depression, anemia, impotence, gastrointestinal ailments, infections, and nervous system disorders [27]. R. rosea is rich in phenolic compounds, known to have strong antioxidant properties [28] (Figure 6). …”
Section: Antiagingmentioning
confidence: 99%